I am having trouble with this.

Add (simplify if possible)

(x^2 + 11x)/(x^2 - 3x) + (x^2 - 6x)/(x^2 - 3x)

I actully came up with two possible answers.

(2x+5)/x-3 and (2x^2-5)/x-6x

I'm not sure which answer is correct.

1 answer

The denominators of the two added terms can be written x(x-3). The x^2-6x term can be written x(x-6). Therefore
(x^2 + 11x)/(x^2 - 3x) + (x^2 - 6x)/(x^2 - 3x) = [x(x+11) + x(x-6)]/[(x(x-3)]
Cancel out the x terms and you get
(2x-5)/(x-3)
Similar Questions
  1. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  2. Simplify 8a − 2a.Simplify 12e − 5f − 7e +3f. Simplify 9x + 3y − 6 − 5x + 4y −3. Simplify 9/11z − 4/11z. Simplify
    1. answers icon 4 answers
  3. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
    1. answers icon 1 answer
more similar questions